Analysis of the Implementation of ISO 9001: 2015 Quality Management System to Improve Service Quality (Case Study at Sea Shipload Expedition Company in Waingapu) - Fitria Dwi Febrianti; Firmike Lidyatami Radja (International Journal of Science and Environment (IJSE), 2025)
This study aims to analyze the implementation of ISO 9001:2015 Quality Management System in a ship cargo expedition company in Waingapu, East Nusa Tenggara. The focus of this research is how the implementation of this standard can improve the quality of the company's services. The method used in this research is a qualitative approach with data collection techniques through observation, in-depth interviews, and document analysis. The research was conducted at PT EMKL X which has implemented ISO 9001: 2015 since 2023. The results showed that the implementation of ISO 9001: 2015 has a positive impact on the quality of service and operational efficiency of the company. This quality improvement can be seen from the consistency of services provided, higher customer satisfaction, and an increase in the number of customers. Employees became more involved in the quality improvement process through training and a better understanding of standard operating procedures. In addition, the implementation of ISO 9001:2015 also improves the company's image and reputation in the eyes of customers and business partners. Thus, this study concludes that the implementation of ISO 9001:2015 is effective in improving the service quality of ocean freight forwarders, as well as providing a competitive advantage in the logistics industry.